The center is Jesus Christ himself : essays on revelation, salvation & evangelization in honor of Robert P. Imbelli - Meszaros, Andrew (The Catholic University of America Press, 2021)
"This collection of essays honoring scholar Robert P. Imbelli, longtime professor of systematic theology at Boston College, delineates the major contours of a Christocentric Catholic theology that anchors its various subdisciplines, such as dogmatic, moral, biblical, and historical theology"--